2021
DOI: 10.1055/s-0041-1733915
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Utility of Measuring Lactate Levels in Patients with Sepsis and Septic Shock?

Abstract: Elevations in blood lactate concentrations have been studied in sepsis and other disease states for decades and are well known to be associated with increased mortality. Many studies have also demonstrated the prognostic accuracy of serial lactate levels, and some have suggested that lactate clearance may be a useful therapeutic target for resuscitation. Lactate measurements have therefore gained an increasingly prominent role in sepsis definitions, screening protocols, management guidelines, and quality measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 115 publications
0
13
0
1
Order By: Relevance
“…In our study, elevated expression of IL-6 was observed in the lung tissue from LPS-animals probably contributing to significant higher mPAP overtime in this group. Furthermore, elevated lactate levels, decreased base excess and lower pH values may reflect tissue hypoxia and changes in lactate metabolism [ 32 ]. Especially elevated lactate levels over time are associated with higher mortality in critical ill patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, elevated expression of IL-6 was observed in the lung tissue from LPS-animals probably contributing to significant higher mPAP overtime in this group. Furthermore, elevated lactate levels, decreased base excess and lower pH values may reflect tissue hypoxia and changes in lactate metabolism [ 32 ]. Especially elevated lactate levels over time are associated with higher mortality in critical ill patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, elevated lactate levels, decreased base excess and lower pH values may reflect tissue hypoxia and changes in lactate metabolism [ 32 ]. Especially elevated lactate levels over time are associated with higher mortality in critical ill patients [ 32 ]. In addition, the drops in the white blood cell count and thrombocytes are also common in sepsis-induced ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have shown that when serum Lac is elevated in sepsis patients, the patients tend to have poorer prognosis and higher mortality. 73 , 74 An initial Lac ⩾4.0 mmol/L was associated with a six-fold increased risk of mortality in the acute phase 22 and to some extent represented hypoperfusion in the tissues of septic patients, which was included in the 2016 sepsis and septic shock guidelines for early identification. 1 In patients with septic shock, the initial Lac level and 6-h Lac clearance are associated with 28-day mortality, and it is suggested that Lac should be normalized within 6 h after fluid resuscitation, 23 which can reduce patient mortality, and early normalization of Lac and Lac clearance greater than 50% are reliable predictors of survival in patients with sepsis.…”
Section: Lactic Acid (Lac)mentioning
confidence: 99%
“…Die Leitlinien schlagen daher auch vor, dass die hämodynamische Stabilisierung eine Normalisierung des Laktatwerts anstreben sollte [4,9]. Es sei jedoch darauf hingewiesen, dass eine Laktatazidose nicht automatisch auf eine Gewebehypoxie hindeutetdie zugrunde liegenden Pathomechanismen sind komplex [12].…”
Section: Weitere Kreislaufstabilisierungunclassified